The effects of diet, breast-feeding and weaning on caries risk for pre-term and low birth weight children - E. S. DAVENPORT, C. LITENAS, P. BARBAYIANNIS & C. E. S. WILLIAMS (Paediatric Dentistry, 2004)
The aims of this study were to determine the prevalence of dental disease in 3–4-year-old children born pre-term and low birth weight (PLBW) in East London, UK, to make comparisons with normal birth weight children (NBW), and to investigate the impact of dietary habits on the development of dental caries in primary teeth.